P331 Composite outcomes in Crohn's disease: a systematic review and meta-analysis of observational studies. (21st January 2022) - Estevinho, M M; Sottomayor, C; Alves, C; Santago, M; Ministro, P; Lago, P; Correia, L; Gonçalves, R; Carvalho, D; Portela, F; Dias, C C; Dignass, A; et al.
Abstract: Background: Observational studies are essential to analyse outcome reporting in inflammatory bowel disease. However, such studies are usually heterogeneous. Therefore, the development of core outcome sets to be included in future observational studies is of major importance. Composite and aggregate outcomes (in which an event is classified by the presence of any one or by the combination of every individual variable under assessment, respectively) allow maximizing the statistical power of observational studies. A systematic review and meta-analysis were performed to assess composite and aggregate outcomes in observational studies for Crohn's disease (CD) and to evaluate whether the number and type of variables affect the frequency of the outcome. Methods: Three online databases (PubMed, Scopus and Web of Science) were searched to identify observational studies that enrolled CD patients and evaluated a composite or aggregate outcome. The proportion of patients achieving the outcome was determined and a random-effects meta-analysis was performed to evaluate how the frequency of each outcome varied according to the reporting of predefined variables. Results: From the, 10.257 identified records, 46 were included in the systematic review and, 38 in the meta-analysis. The median frequency of composite and aggregate outcomes was, 0.445 [95% confidence interval (CI), 0.389–0.501] and, 0.140 [95% CI, 0.000-, 0.211], respectively. When comparing composite outcomes by the number of included variables, the frequency was, 0.271 [95% CI, 0.000-, 0.405] and, 0.698 [95% CI, 0.651–0.746], for one and six variables, respectively. The frequency of the composite outcome varied according to the set of variables being reported. Specific pairs of predefined variables had a significant effect on the frequency of composite outcomes. Conclusion: Composite outcomes with an increasing number of variables and those including the variables "surgery" and "steroids" presented higher frequencies. Moreover, specific variables and pairs of variables had a clear effect on the frequency of composite outcomes. Taking this information into account, future efforts must be made to standardize CD outcome reporting, a yet unmet need.